COVID-19 in the Environment : impact, concerns, and management of Coronavirus - Rawtani, Deepak; Hussain, Chaudhery Mustansar; Khatri, Nitasha (Elsevier, 2022)
COVID-19 in the Environment: Impact, Concerns, and Management of Coronavirus highlights the research and technology addressing COVID-19 in the environment, including the associated fate, transport, and disposal. It examines the impacts of the virus at local, national, and global levels, including both positive and negative environmental impacts and techniques for assessing and managing them. Utilizing case studies, it also presents examples of various issues around handling these impacts, as well as policies and strategies being developed as a result. Organized into six parts, COVID-19 in the Environment begins by presenting the nature of the virus and its transmission in various environmental media, as well as models for reducing the transmission. Section 2 describes methods for monitoring and detecting the virus, whereas Sections 3, 4, and 5 go on to examine the socio-economic impact, the environmental impact and risk, and the waste management impact, respectively. Finally, Section 6 explores the environmental policies and strategies that have comes as a result of COVID-19, the implications for climate change, and what the long-term effects will be on environmental sustainability.